Elastic scattering of 96 MeV neutrons from iron, yttrium, and lead - A. Öhrn (2018)
Data on elastic scattering of 96 MeV neutrons from Fe56, Y89, and Pb208 in the angular interval 10-70° are reported. The previously published data on Pb208 have been extended, as a new method has been developed to obtain more information from data, namely to increase the number of angular bins at the most forward angles. A study of the deviation of the zero-degree cross section from Wick's limit has been performed. It was shown that the data on Pb208 are in agreement with Wick's limit while those on the lighter nuclei overshoot the limit significantly. The results are compared with modern optical model predictions, based on phenomenology and microscopic nuclear theory. The data on Fe56, Y89, and Pb208 are in general in good agreement with the model predictions. © 2008 The American Physical Society.